\[x² - (3a + 4)x + 12a = 0\]
\[D = \left( - (3a + 4) \right)^{2} - 4 \cdot 1 \cdot 12a =\]
\[= 9a^{2} + 24a + 16 - 48a =\]
\[= 9a^{2} - 24a + 16 = (3a - 4)^{2}\]
\[1)\ При\ D = 0:\]
\[3a - 4 = 0\]
\[3a = 4\]
\[a = \frac{4}{3}\text{\ \ }\]
\[a = 1\frac{1}{3}.\]
\[Получаем:\]
\[x = \frac{3a + 4}{2} = \frac{3 \cdot \frac{4}{3} + 4}{2} =\]
\[= \frac{4 + 4}{2} = \frac{8}{2} = 4.\]
\[2)\ \ При\ D > 0;\ a \neq 1\frac{1}{3}:\]
\[x_{1,2} = \frac{3a + 4 \pm \sqrt{(3a - 4)^{2}}}{2} =\]
\[= \frac{3a + 4 \pm |3a - 4|}{2}\]
\[x_{1} = \frac{3a + 4 + 3a - 4}{2} =\]
\[= \frac{6a}{2} = 34;\]
\[x_{2} = \frac{3a + 4 - 3a + 4}{2} = \frac{8}{2} = 4.\]
\[Ответ:если\ a = 1\frac{1}{3};то\ x = 4;\]
\[\ \ \ \ \ \ \ \ \ \ \ \ \ если\ a \neq 1\frac{1}{3};\]
\[то\ \ x_{1} = 3a\ или\ x_{2} = 4.\]